From graphite oxide to highly water dispersible functionalized graphene by single step plant extract-induced deoxygenation - Mhamane, Dattakumar; Ramadan, Wegdan; Fawzy, Manal; Rana, Abhimanyu; Dubey, Megha; Rode, Chandrashekhar; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra (Green Chemistry, 2011)
We report a single step facile synthesis of highly water dispersible functionalized graphene nanosheets by plant extract-induced deoxygenation of graphite oxide (GO). The results of various characterizations reveal that the properties of such plant extract-converted graphene nanosheets (PCGN) are comparable to chemically converted graphene nanosheets (CCG). These results open a green route to the emerging graphene-based technologies.

Facile one-pot synthesis of aliphatic bridged diaryloxy compounds, cyclic and crown ethers under mild conditions - Sakate, Sachin; Kamble, Sumit; Chikate, Rajiv; Rode, Chandrashekhar (Supramolecular Chemistry, 2017)
We report here the facile, room temperature, catalyst free, one pot synthesis of aliphatic bridged diaryloxy compounds, cyclic and crown ethers. Anhydrous potassium carbonate (K2CO3) as a mild base along with dimethyl sulfoxide generates the phenoxide ion which facilitates the nucleophilic substitution of bromoalkanes to yield the corresponding crown ethers.